Progress of hydrogenation engineering in crystalline silicon solar cells: a review. (10th November 2022) - Song, Lihui; Hu, Zechen; Lin, Dehang; Yang, Deren; Yu, Xuegong
Abstract: Crystalline silicon solar cells are always moving towards 'high efficiency and low cost', which requires continuously improving the quality of crystalline silicon materials. Nevertheless, crystalline silicon materials typically contain various kinds of impurities and defects, which act as carrier recombination centers. Therefore these impurities and defects must be well controlled during the solar cell fabrication processes to improve the cell efficiency. Hydrogenation of crystalline silicon is one important method to deactivate these impurities and defects, which is so-called 'hydrogenation engineering' in this paper. Hydrogen is widely reported to be able to passivate diverse defects like crystallographic defects, metallic impurities, boron-oxygen related defects and etc, but the effectiveness of hydrogen passivation depends strongly on the processing conditions. Moreover, in this decade, advanced hydrogenation technique has been developed and widely applied in the photovoltaic industry to significantly improve the performance of silicon solar cells. As the research on hydrogenation study has made a significant progress, it is the right time to write a review paper on introducing the state-of-the-art hydrogenation study and its applications in photovoltaic industry. The paper first introduces the fundamental properties of hydrogen in crystalline silicon and then discusses the applications of hydrogen on deactivating/inducing typical defects (e.g. dislocations, grain boundaries, various metallic impurities, boron–oxygen related defects and light and elevated temperature induced degradation defect) in p- and n-type crystalline silicon, respectively. At last, the benefits of hydrogenation engineering on the next-generation silicon solar cells (e.g. tunnel oxide passivated contact (TOPCon) and silicon heterojunction (SHJ) solar cells) are discussed. Overall, it was found that hydrogen can deactivate most of typical defects (sometimes induce defect) in n- and p-type crystalline silicon, leading to a significant efficiency enhancement in passivated emitter rear contact, TOPCon and SHJ solar cells. In conclusion, the paper aims to assist young researchers to better understand hydrogenation research.